Monitoring of suction bucket jackets for offshore wind turbines: Dynamic load bearing behaviour and modelling. (July 2020) - Penner, Nikolai; Grießmann, Tanja; Rolfes, Raimund
Abstract: Suction bucket foundations for offshore wind turbines (OWT) have considerable advantages compared to conventional foundation types: Due to the installation process with dead weight and applied negative pressure, noise from pile driving can be completely avoided. In addition, the installation process of the whole substructure, consisting of the buckets connected to the jacket, can be carried out in one work step, which increases efficiency. A prototype of the suction bucket jacket was installed in the wind park 'Borkum Riffgrund 1' (North Sea) in August 2014. Due to the pre-installed and comprehensive measuring system, it was possible to monitor all installation and operating phases. The data analysis of a storm event show an amplitude and frequency-dependent behaviour of the soil stiffness and the suction bucket foundation without wind turbine. In the frequency range of the first and second eigenfrequency (0.2 Hz < f < 5 Hz), the system behaves linearly. Here, the Frequency Domain Decomposition is used for identification and monitoring. For the lower frequency band (0.05 Hz < f < 0.2 Hz) where higher forces and displacements occur, a non-linear multilayer perceptron is chosen to model the non-linear relations between measurements. By applying two mathematical models for the relevant frequency ranges, all the information from the measurement data can be used for system identification and novelty detection under varying environmental conditions. Highlights: Suction Bucket Jacket under offshore conditions with comprehensive measuring system. Dynamic load bearing behaviour and soil stiffness identified by monitoring. Operational modal analysis by Frequency Domain Decomposition. Influence of environmental conditions on the dynamic structural behaviour. Autoregressive multilayer perceptron to connect measurements in low frequency range.